FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK IBU DALAM MELINDUNGI KELUARGA DARI PAPARAN ASAP ROKOK - Rahayu Sitorus; Bagoes Widjanarko; Aditya Kusumawati (Jurnal Kesehatan Masyarakat, 2019)
Background: Exposure from cigarette smoke is dangerous because it can cause lung cancer and cardiovascular damage, and can damage lung and respiratory health in children. The purpose of this study was to analyze factors related to maternal practice in an effort to protect families from exposure to cigarette smoke. Methods:  This type of research is descriptive analytic, quantitative approach, cross sectional research design with a sample of 97 respondents (mothers who have children and husbands in Sawah Besar Village, Gayamsari District, Semarang City). the instrument used in the form of a questionnaire with interviews. Data analysis used is univariate and bivariate with chi-square test. Results: The results showed that the respondent's age was dominated by age ≥ 41 years with the last education graduating from junior high school / equivalent. Respondents did not work at 62.9%. The results showed that the age of the respondent (p = 0.031), knowledge (p = 0.005) and perceived barriers (p = 0.012) were related to the practice of mothers in an effort to protect families from exposure to cigarette smoke. Educational level variables (p = 0.685), employment (p = 0.685), perceptions of vulnerability (p = 0.878) and perceptions of seriousness (p = 0.501) were not related to maternal practices in an effort to protect families from exposure to cigarette smoke.  Conclusion: It is necessary to increase parents' awareness of mothers in particular to the dangers of cigarette smoke to family members and the existence of more supervision on the activities of family members who have the opportunity to be exposed to cigarette smoke.